Development of a new wheelchair for wheelchair basketball players in the Netherlands - Berger, M. A. M.; van Nieuwenhuizen, M.; van der Ent, M.; van der Zande, M. (Procedia Engineering, 2012)
The aim of the development of a new basketball wheelchair was to reduce the weight of the frame, to develop a program to fit anthropometric measurements to design a custom made wheelchair and to develop high-end wheels to increase propulsion efficiency by reducing rolling resistance. The redesigning process resulted in a frame which is 30% lighter than current aluminium wheelchair frames, a program that links anthropometric data to a CAD model of wheelchairs and a new wheel. Several tests were performed to evaluate the new wheelchair. The tests showed promising results with respect to improving both technical performance combined with the athlete's performance.